A study of the manufacture of visibility for South African black women artist practicing in post-apartheid South Africa by intersecting commercial, academic, and social media engagement - Anguria, Lois (My University, 2022)
This thesis examines the visibility of Black women practicing as artists in South Africa. This is done by reviewing the demographics of artists represented by the most prominent galleries, at local and international art fairs, in South African auction consignments, and museum solo exhibition programmes. This thesis argues that the visibility of South African Black women in visual art is markedly diminished when compared to other demographics in the industry. Theories around visibility and hypervisibility are employed to frame how these function in the South African art industry. This is further complicated by the racialised history of South Africa and the marginalised visibility that Black women have been limited to. Senzeni Marasela and Tony Gum are the main artists discussed as case studies. Marasela’s longevity in the industry, and especially in academic spaces, contrasts with the limited and inconsistent visibility she has had in her career. Gum’s sharp trajectory in a short time combined with a determination to reject notions of Black womanhood and African art, offer arguments to alternatives for how visibility can be handled, particularly using social media.
A thesis submitted to the Faculty of Humanities in fulfilment of the requirement for the degree of Doctor of Philosophy in the History of Art, University of the Witwatersrand, Johannesburg